Activity of fly ash as an indicator of their modifying ability. Issue 1 (March 2020) - Markova, I Yu; Bezrodnykh, A A; Markov, A Yu; Strokova, V V; Stepanenko, M A
Abstract: The article shows the possibility of using fly ash as an active component of binders of various compositions used in the design of composites for road construction purposes. This study was conducted on the basis of the data on the distribution and concentration of acid-base centers on the surface, sorption capacity, specific surface area, and morphological features of dispersed particles of technogenic raw materials. The study substantiates the feasibility of using ashes as a modifying component of low-calcium composites for inorganic binders (cement) due to the high pozzolanic activity, high-calcium composites for organic binders (bitumen emulsions) due to "inertness" and surface smoothness.